Managed care and monopoly power : the antitrust challenge - Haas-Wilson, Deborah (Harvard University Press, 2003)
Annotation As millions of Americans are aware, health care costs continue to increase rapidly. Much of this increase is due to the development of new life-sustaining drugs and procedures, but part of it is due to the increased monopoly power of physicians, insurance companies, and hospitals, as the health care sector undergoes reorganization and consolidation. There are two tools to limit the growth of monopoly power: government regulation and antitrust policy. In this timely book, Deborah Haas-Wilson argues that enforcement of the antitrust laws is the tool of choice in most cases. The antitrust laws, when wisely enforced, permit markets to work competitively and therefore efficiently. Competitive markets foster low prices and high quality. Applying antitrust tools wisely, however, is a tricky business, and Haas-Wilson carefully explains how it can be done. Focusing on the economic concepts necessary to the enforcement of the antitrust laws in health care markets, Haas-Wilson provides a useful roadmap for guiding the future of these markets.